Green practices at Café towards customer satisfaction in Klang Valley / Nur Qamarina Raffikhul Houssain, Asniza Hamimi Abdul Tharim and Suriani Ngah Abdul Wahab - Raffikhul Houssain, Nur Qamarina; Abdul Tharim, Asniza Hamimi; Ngah Abdul Wahab, Suriani (2022)
Green restaurants are defined as restaurants that implement sustainable practices in its daily operation in order to reduce the negative impact to the environment. Previous studies showed that the implementation of green practices in restaurants could help to improve the business growth in a sustainable manner, provide pleasant ambience and enjoyment to the customer as well as other perceptions of satisfaction. Nowadays, the concepts of green practices at restaurants are gaining attention due to global warming and ecological degradation. Although the modes of green consumption and awareness of the environment are increasing, several studies found that the implementation of green practices at restaurants are still lacking. Due to heavy workloads and busy schedules, people tend to spend most of their time working to meet the deadline and fulfill the employers' expectation. This will result in an extensive eating out habits among the working people. Therefore, this paper aims to review the previous research related to green practices at restaurants by using a Systematic Literature Review (SLR). This paper concludes that green practices in terms of the food and beverage, service, management and environment can be used as one of the strategies to increase the customer satisfaction. These findings are beneficial to the restaurateurs as they can make improvements in areas that lead to a greater satisfaction to customers' restaurant experience as well as increase their bottom line.